AMELIORASI DAN PEYORASI DALAM BAHASA MADURA DI KABUPATEN KUBU RAYA - Nakip, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This research is based on the dynamic or change in nature of the language. It is this nature that usually causes a change of a language, especially meaning. In this case, the change in meaning that occur are amelioration and peyoration changes. These apply to every language in Indonesia, especially Madurese language. Therefore, this research aims to describe the change in the meaning of the word amelioration and peyoration and describes the function of change the meaning of ameliorate and peyoration in Madurese language in Kabupaten Kubu Raya. This research was conducted at Dusun Karya Dua, Desa Kuala Dua, Kecamatan Sungai Raya, Kabupaten Kubu Raya. The research method that used was descriptive method in the form of qualitative. Technique of collecting data that used were interview technique, record, and record. Data collection tools that used were stationery, tape recorder, and auxiliary instruments. Data an¬alysis techniques that used were comparative techniques and grammatical analysis. The function of amelioration changes, including eliminating prejudice, cultural and religious adjustments, beauty, beautification of appearance, and needs. Functions of peyoration change, including cursing, rejection, expression of irritation, self-reliance, boasting, and flexibility.  Keywords: Change of Meaning, Amelioration, Peyorasi, Function of Change, Madurese Language